Implications of the Meeting of religion and new media for contemporary da'wah in Indonesia - Mudhofi, M; Adeni, Adeni; Karim, Abdul (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - The transformative power of new media has revolutionized the practice of Islamic da'wah. This article examines the implications of the intersection of religion and new media for contemporary da'wah practices.Method - This study uses qualitative research with a new media and da'wah approach. Data was obtained by online observation of da’wah social media that featured or involved several da’wah figures in Indonesia.Result - This study found that testing the 5 Cs (Communication, Collaboration, Community, Creativity, and Convergence) that characterize new media shows a different form of da'wah in new media from the construct of da'wah in the conventional era. In the new media era, for example, da'wah is understood as open communication that allows the preacher and the recipient to exchange messages simultaneously. In new media, da'wah is also a collaborative activity that allows everyone to collaborate to support a da'wah idea. New media-based da'wah is also characterized by the existence of various da'wah communities spread across multiple platforms, the creativity of various actual content that is by various issues developing in society, as well as the combination of numerous media which makes da'wah content in new media available completely, openly, and easily accessed.Implication - Academically, this study has implications for enriching preaching theories in the contemporary world, while practically, this study has implications for the importance of preachers in adapting to the dynamics produced by new media.Originality/Value - The originality of this research lies in its novelty, which focuses on changes in preaching due to new media that have received little attention from previous researchers.***Tujuan - Media baru telah mengubah praktik dakwah Islam. Artikel ini bertujuan untuk mengkaji implikasi pertemuan agama dan media baru terhadap praktik dakwah kontemporer.Metode - Studi ini menggunakan jenis penelitian kualitatif dengan pendekatan media baru dan dakwah. Data diperoleh melalui observasi online terhadap website dan media sosial dakwah yang menampilkan atau melibatkan beberapa tokoh dakwah di Indonesiat.Hasil - Studi ini menemukan bahwa pengujian 5 C (Communication, Collaboration, Community, Creativity, dan Convergence) yang menjadi ciri media baru menunjukkan adanya bentuk dakwah yang berbeda dalam new media dengan konstruk dakwah pada era konvensional. Di era media baru misalnya, dakwah dipahami sebagai komunikasi terbuka yang memungkinkan pendakwah dan penerimanya bertukar pesan secara simultan. Selain itu, dalam media baru, dakwah juga dipahami sebagai kegiatan kolaboratif yang memungkinkan semua orang bekerja sama untuk mendukung suatu gagasan dakwah. Dakwah berbasis media baru juga ditandai dengan adanya berbagai komunitas dakwah yang tersebar di berbagai platform, kreativitas berbagai konten aktual yang sesuai dengan berbagai isu yang berkembang di masyarakat, serta perpaduan berbagai media yang menjadikan dakwah di media baru bekerja dalam mode yang utuh, terbuka, dan mudah diaskses.Implikasi - Secara akademis studi ini berimplikasi pada pengayaan teori-teori dakwah dalam dunia kontemporer sedangkan secara praktis studi ini berimplikasi pada pentingnya pendakwah dalam beradaptasi dengan dinamika yang dihasilkan oleh media baru.Orisinalitas/Nilai - Keaslian penelitian ini terletak pada kebaruannya yang berfokus pada perubahan dakwah akibat media baru yang belum banyak mendapat perhatian dari peneliti sebelumnya.